Affective affordances in technology-mediated language teaching and learning - Anwar Ahmed (Technology in Language Teaching & Learning)
This article focuses on the intersection of technology and pedagogy through the lens of affect/ emotion. It highlights why technology-mediated teaching and learning require new ways of thinking about emotionality in educational contexts. To develop a nuanced understanding of what technology can and cannot do, we can draw insights from the recent affective turn in humanities and the social sciences, which wants us to look at human emotions as socially constructed, biologically rooted, physically distributed, and agentically complex. Building on the recent scholarship on critical affect/ emotion studies, I advocate a view of human emotionality that rejects the idea of emotion as an individual’s internal property or as a total social force outside the individual. The goal of this discussion is to bring more attention to affective affordances that will hopefully provide some pedagogical implications for technology-mediated spaces.